A new species of Notonyx A. Milne-Edwards 1873 (Crustacea: Decapoda: Brachyura: Goneplacidae) from Maluku, Indonesia - Rahayu, Dwi Listyo (Zootaxa, 2011)
A new species of Notonyx A. Milne-Edwards, 1873 (Crustacea: Decapoda: Brachyura: Goneplacidae) is described from Maluku, Indonesia and differs from closely related species, N. latus Ng & Clark, 2008 and N. sagittifer Ng & Clark 2010, in that the male abdomen is relatively narrower and the tip of the male second gonopod is sickled-shaped.